Solid amine resin adsorbent as well as preparation method and application thereof

By reacting with ethane-1,2-diamine hydrochloride on a macroporous chloromethylated resin and treating it with sodium hydroxide aqueous solution, a solid amine resin adsorbent with high amine-based exchange capacity was prepared, which solved the problems of high regeneration energy consumption and incomplete absorption in the existing natural gas decarbonization technology, and achieved efficient and stable carbon dioxide adsorption effect.

CN119608122AActive Publication Date: 2025-03-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411831893.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-14
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing natural gas decarbonization technology has problems such as high regeneration energy consumption, serious equipment corrosion, poor volatility and recycling performance of alcohol amine solvents, especially incomplete absorption in low carbon dioxide natural gas, and requires combined processes to perform decarbonization.

Method used

A large pore chloromethylated resin was used as a support, and a solid amine resin adsorbent with high amine group exchange capacity was prepared by heating reaction with ethane-1,2-diamine hydrochloride under mild conditions, combined with the soaking and drying steps of sodium hydroxide aqueous solution, thereby avoiding the resin cross-linking problem in graft modification.

Benefits of technology

The amine-based exchange capacity and carbon dioxide adsorption capacity of solid amine resin adsorbent are improved. The amine-based exchange capacity can be as high as 11.2 mmol/g and the carbon dioxide adsorption capacity can be as high as 170 mg/g. After 40 cycles and regeneration, the adsorption capacity remains almost unchanged, which significantly improves the adsorption performance and use cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608122A_ABST
    Figure CN119608122A_ABST
Patent Text Reader

Abstract

The invention provides a solid amine resin adsorbent as well as a preparation method and application thereof, and relates to the technical field of low-concentration carbon dioxide trapping. The method for preparing the solid amine resin adsorbent by taking the macroporous chloromethylated resin as the carrier is simple in process and mild in reaction condition, the ethane-1, 2-diamine hydrochloride is used as a grafting reagent, the problem of resin crosslinking generated in a grafting modification reaction is avoided, and the solid amine resin adsorbent is prepared. The effective utilization rate of the grafting reagent and the amino exchange capacity of the solid amine resin adsorbent are improved, the amino exchange capacity can reach up to 11.2 mmol / g, the carbon dioxide adsorption capacity can reach up to 170mg / g, and compared with an impregnation method, the solid amine resin adsorbent prepared by the grafting modification method has the advantages that the amino reagent is not easy to lose, the adsorption performance after regeneration is good, and the adsorption efficiency is high. And the carbon dioxide adsorption capacity is almost unchanged after 40 times of cyclic regeneration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon dioxide capture, and in particular to a solid amine resin adsorbent with high amine exchange capacity, a preparation method thereof, and application thereof in decarbonization of gas with low carbon dioxide content. Background Art

[0002] As a clean energy with abundant reserves, natural gas has lower carbon dioxide emissions and higher unit calorific value when burned compared with traditional fossil energy, and can meet society's significant demand for low-carbon energy. Therefore, the status and role of natural gas in the global energy system are becoming increasingly prominent.

[0003] my country's latest national standard for natural gas (GB 17820-2018) stipulates that the molar fraction of carbon dioxide in Class I natural gas is required to be ≤3.0%, and the molar fraction of carbon dioxide in Class II natural gas is required to be ≤4.0%; therefore, most natural gas must be strictly decarbonized before being transported to the commercial pipeline network; the methods currently suitable for natural gas decarbonization mainly include solvent absorption, pressure swing adsorption, membrane separation, etc., among which the alcohol amine solvent absorption method is the most widely used natural gas decarbonization method in industry. The alcohol amine solvent absorption method has the advantages of mature technology, large processing capacity, and high selectivity, but it still has problems such as high regeneration energy consumption, serious equipment corrosion, alcohol amine solvent volatilization and poor recycling performance. For low-carbon dioxide content natural gas with a carbon dioxide content of less than 15%, there is still the problem of incomplete absorption, and a combined process is required for decarbonization. Therefore, it is of great practical significance to develop a low-carbon dioxide content natural gas decarbonization technology with high efficiency, long life, and low energy consumption.

[0004] In recent years, the technology of removing carbon dioxide by solid-state amine adsorption has developed rapidly. By modifying the amine group into the porous material to have the ability to adsorb carbon dioxide, this solid-state amine adsorbent effectively reduces the corrosiveness of organic amines and the volatilization loss during use. The uniform pore distribution, high specific surface area and pore volume inside the porous material can promote the diffusion of carbon dioxide and improve the adsorption efficiency. At the same time, the low heat capacity of solid-state amine can also reduce the energy consumption of the regeneration process. It is an ideal adsorbent for decarbonization of low carbon dioxide content gases.

[0005] There are many reports on the use of solid amine adsorbents for low-concentration carbon dioxide adsorption. For example, CN102343254A involves a room-temperature carbon dioxide solid amine adsorbent, which adsorbs low-concentration carbon dioxide (content of 1.5-2.2 vol%) at room temperature, and the adsorption capacity of carbon dioxide reaches more than 2.45 mmol / g. CN112337448B involves a solid amine hollow fiber and a preparation method thereof, wherein a porous hollow fiber is prepared by a steam-immersion induced phase conversion method; an amine group is grafted into the porous tube wall of the hollow fiber by reaction to obtain a solid amine hollow fiber, a gas containing carbon dioxide is passed into one end of the hollow fiber tube, and the gas passes through the porous tube wall and flows out from the other end of the hollow fiber tube, wherein the carbon dioxide is adsorbed in the hollow fiber by the amine group, and then the adsorbed carbon dioxide can be resolved by heating the solid amine hollow fiber to complete regeneration. CN105195113A relates to a solid amine adsorbent for capturing low-concentration carbon dioxide at room temperature, a preparation method and an application thereof. The adsorbent is a macroporous adsorption resin modified by a liquid organic amine and a surfactant. The organic amine and the surfactant are dissolved in an organic solvent, and the macroporous adsorption resin is added. The reaction is carried out on a rotary evaporator for a period of time, so that the organic amine and the surfactant are impregnated into the pore structure of the resin carrier, and low-concentration carbon dioxide is adsorbed at room temperature, and the adsorption capacity can reach 165.5 mg / g; the preparation methods of the solid amine adsorbent provided by the above patents are all impregnation methods. The amine-based reagents of the solid amine adsorbents prepared by this method are easy to lose, the service life is short, and additional deamination purification equipment is required. The grafting modification method is used to connect the grafting reagent to the macroporous adsorption material in the form of a chemical bond, which can effectively improve the stability of the solid amine adsorbent, extend the service life, and reduce equipment investment and operating costs. However, the grafting reagent is prone to cross-linking during grafting modification, which makes the amine exchange capacity of the solid amine resin adsorbent low, and reduces the carbon dioxide adsorption capacity. Summary of the invention

[0006] In view of the deficiencies of the prior art, the present invention provides a solid amine resin adsorbent for decarbonization of low carbon dioxide content gas, and a preparation method and application thereof. The method for preparing a solid amine resin adsorbent using a macroporous chloromethylated resin as a carrier has a simple process and mild reaction conditions. Ethane-1,2-diamine hydrochloride is used as a grafting reagent, which avoids the resin cross-linking problem generated in the grafting modification reaction, improves the effective utilization rate of the grafting reagent and the amine exchange capacity of the solid amine resin adsorbent, and the amine exchange capacity can be as high as 11.2 mmol / g, and the carbon dioxide adsorption capacity can be as high as 170 mg / g. Compared with the impregnation method, the amine reagent of the solid amine resin adsorbent prepared by the grafting modification method is not easy to lose, and the adsorption performance is good after regeneration. The carbon dioxide adsorption capacity remains almost unchanged after 40 cycles of regeneration.

[0007] One of the purposes of the present invention is to provide a solid amine resin adsorbent.

[0008] The second object of the present invention is to provide a method for preparing the solid amine resin adsorbent.

[0009] The third object of the present invention is to provide an application of the solid amine resin adsorbent.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] In a first aspect, the present invention provides a solid amine resin adsorbent, the structure of the solid amine resin adsorbent is as follows:

[0012]

[0013] In a second aspect, the present invention provides a method for preparing the above-mentioned solid amine resin adsorbent, comprising the following steps:

[0014]

[0015] (1) Macroporous chloromethylated resin and ethane-1,2-diamine hydrochloride in the presence of a solvent for heating reaction, after the reaction is completed, the temperature is lowered to room temperature and the solution in the reaction system is filtered, and the resin is washed with water until the pH of the water is neutral;

[0016] (2) Soaking the resin obtained in step (1) with an aqueous sodium hydroxide solution, separating the resin and washing the resin with water until the pH of the water is neutral, and drying to obtain a solid amine resin adsorbent.

[0017] In some embodiments, the macroporous chloromethylated resin in step (1) has a particle size of 500-800 μm and a specific surface area of ​​20-45 m 2 / g;

[0018] In some embodiments, the pore size of the macroporous chloromethylated resin in step (1) is 10-25 nm, and the pore volume is 0.05-0.3 cm 3 / g.

[0019] In some embodiments, in step (1), the solvent is one or more selected from anhydrous tetrahydrofuran, acetonitrile, dichloromethane, 1,4-dioxane, N,N'-dimethylformamide and dimethyl sulfoxide, preferably anhydrous dimethyl sulfoxide.

[0020] In some embodiments, in step (1), the amount of solvent added is 200-400 mL relative to 50 g of chloromethylated resin.

[0021] In some embodiments, in step (1), the mass ratio of the macroporous chloromethylated resin to ethane-1,2-diamine hydrochloride is 1:0.5 to 1:1.

[0022] In some embodiments, in step (1), the reaction temperature is 60-80° C., and the reaction time is 12-24 h.

[0023] In some embodiments, in step (2), the equivalent concentration of the sodium hydroxide aqueous solution is 1-2N.

[0024] In some embodiments, in step (2), the soaking time is 12-24 hours.

[0025] Specifically, the preparation method of the solid amine resin adsorbent comprises the following steps:

[0026] (1) adding chloromethylated resin, ethane-1,2-diamine hydrochloride and anhydrous dimethyl sulfoxide into a round-bottom flask, and then heating to 60-80° C. for reaction for 12 hours. After the reaction is completed, cooling to room temperature and filtering the solution in the reaction system, and washing the resin with deionized water until the pH of the washed water phase is neutral;

[0027] (2) Soaking the resin obtained in step (1) in a 2N sodium hydroxide solution for 12 hours, then filtering out the resin and washing the resin with deionized water until the pH of the washed water phase is neutral; and drying the resin in an oven at 120° C. for 6 hours to obtain a solid amine resin adsorbent.

[0028] In a third aspect, the present invention provides a use of the above-mentioned solid amine resin adsorbent in the decarbonization of mixed gas with low carbon dioxide content.

[0029] In some embodiments, the application includes the following steps: loading the solid amine resin adsorbent into an adsorption reactor, adjusting the temperature of the adsorption reactor to a set temperature; passing the carbon dioxide mixed gas from the lower end of the adsorption reactor at a set flow rate and pressure, and discharging it from the upper end after passing through the adsorbent, and connecting the discharged gas to a flue gas monitor to detect the carbon dioxide content in the gas.

[0030] Preferably, the volume content of carbon dioxide in the carbon dioxide mixed gas is ≤15%.

[0031] Preferably, the adsorption temperature is 10-40°C, preferably 20-40°C; the adsorption pressure is 0.1-5.0MPa, preferably 0.1-4.0MPa; the adsorption space velocity is 1000-3000h -1 , preferably 2000-3000h -1 .

[0032] Preferably, the application also includes regeneration of the solid amine resin adsorbent, and the regeneration method is temperature-swing regeneration;

[0033] Preferably, the regeneration temperature is 50-100°C, preferably 70-100°C, and the flow rate is 200-500 mL / min, preferably 400-500 mL / min.

[0034] Technical effect:

[0035] Compared with the prior art, the present invention has the following advantages:

[0036] (1) The synthesis method of solid amine resin adsorbent is simple, the reaction conditions are mild, and the macroporous chloromethylated resin adsorbent material used is easy to prepare.

[0037] (2) Using ethane-1,2-diamine hydrochloride as the grafting agent avoids the resin cross-linking problem generated in the grafting modification reaction, improves the effective utilization rate of the grafting agent and the amine exchange capacity of the solid amine resin adsorbent, the amine exchange capacity can be as high as 11.2 mmol / g, and the carbon dioxide adsorption capacity can be as high as 170 mg / g.

[0038] (3) The solid amine resin adsorbent prepared by the chemical grafting modification method has good stability, the amine-based reagent is not easy to lose, the adsorption performance is good after regeneration, and the service life is long. After 40 cycles of regeneration, the carbon dioxide adsorption capacity remains almost unchanged.

[0039] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is the infrared analysis chart of the solid amine resin adsorbent prepared in Example 4;

[0041] Figure 2 It is the carbon dioxide cyclic adsorption capacity of the solid amine resin adsorbent prepared in Application Example 1. DETAILED DESCRIPTION

[0042] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.

[0043] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.

[0044] Amine exchange capacity: Accurately weigh 0.5000g of solid amine resin adsorbent and put it into a 100mL beaker. Use a pipette to measure 50mL of 0.1mol / L hydrochloric acid solution to soak the resin for 24 hours. Use a pipette to measure 10mL of the soaking mother liquor and transfer it to a 100mL beaker, then dilute it to 50mL with deionized water, use an acid-base potentiometric titrator to reversely titrate to pH=7.0 and calculate the hydrochloric acid concentration in the mother liquor.

[0045] The amine exchange capacity is calculated as follows:

[0046]

[0047] Example 1

[0048] Take 50g of dried macroporous chloromethylated resin (Hebei Kairui Chemical Co., Ltd., particle size 650μm, specific surface area 30.0m 2 / g, pore diameter 20.0nm, pore volume 0.10cm 3 / g) was placed in a 500mL three-necked round-bottom flask, and then 200mL of anhydrous dimethyl sulfoxide and 25g of ethane-1,2-diamine hydrochloride (Shanghai Haohong Biomedicine Technology Co., Ltd.) were added; after the addition was completed, the reaction system was heated to 60°C for reaction for 12 hours, and after the reaction was completed, the temperature was cooled to room temperature and the solution in the reaction system was filtered, and the resin was washed with deionized water until the pH of the washed water phase was neutral; the obtained adsorption resin was soaked in 2N sodium hydroxide solution for 12 hours, and then the resin was filtered out and washed with deionized water until the pH of the washed water phase was neutral, and finally the adsorption resin was placed in an oven at 120°C and dried for 6 hours to obtain a solid amine resin adsorbent with an amine group exchange capacity of 7.7mmol / g.

[0049] Example 2

[0050] Take 50g of dried macroporous chloromethylated resin (Hebei Kairui Chemical Co., Ltd., particle size 650μm, specific surface area 30.0m 2 / g, pore diameter 20.0nm, pore volume 0.10cm 3 / g) was placed in a 500mL three-necked round-bottom flask, and then 200mL of anhydrous dimethyl sulfoxide and 50g of ethane-1,2-diamine hydrochloride (Shanghai Haohong Biomedicine Technology Co., Ltd.) were added; after the addition was completed, the reaction system was heated to 60°C for reaction for 12 hours, and after the reaction was completed, the temperature was cooled to room temperature and the solution in the reaction system was filtered, and the resin was washed with deionized water until the pH of the washed water phase was neutral; the obtained adsorption resin was soaked in 2N sodium hydroxide solution for 12 hours, and then the resin was filtered out and washed with deionized water until the pH of the washed water phase was neutral, and finally the adsorption resin was placed in an oven at 120°C and dried for 6 hours to obtain a solid amine resin adsorbent with an amine group exchange capacity of 9.2mmol / g.

[0051] Example 3

[0052] Take 50g of dried chloromethylated resin (Hebei Kairui Chemical Co., Ltd., particle size 650μm, specific surface area 30.0m 2 / g, pore diameter 20.0nm, pore volume 0.10cm 3 / g) was placed in a 500mL three-necked round-bottom flask, and then 200mL of anhydrous dimethyl sulfoxide and 50g of ethane-1,2-diamine hydrochloride (Shanghai Haohong Biomedicine Technology Co., Ltd.) were added; after the addition was completed, the reaction system was heated to 80°C for reaction for 12 hours, and after the reaction was completed, the temperature was lowered to room temperature and the solution in the reaction system was filtered, and the resin was washed with deionized water until the pH of the washed water phase was neutral; the obtained adsorption resin was soaked in 2N sodium hydroxide solution for 12 hours, and then the resin was filtered out and washed with deionized water until the pH of the washed water phase was neutral, and finally the adsorption resin was placed in an oven at 120°C and dried for 6 hours to obtain a solid amine resin adsorbent with an amine group exchange capacity of 10.0mmol / g.

[0053] Example 4

[0054] Take 50g of dried chloromethylated resin (Hebei Kairui Chemical Co., Ltd., particle size 700μm, specific surface area 40.0m 2 / g, pore diameter 23.0nm, pore volume 0.20cm 3 / g) was placed in a 500mL three-necked round-bottom flask, and then 200mL of anhydrous dimethyl sulfoxide and 50g of ethane-1,2-diamine hydrochloride (Shanghai Haohong Biopharmaceutical Technology Co., Ltd.) were added; after the addition was completed, the reaction system was heated to 80°C for 12 hours, and after the reaction was completed, the temperature was lowered to room temperature and the solution in the reaction system was filtered, and the resin was washed with deionized water until the pH of the washed water phase was neutral; the obtained adsorption resin was soaked in 2N sodium hydroxide solution for 12 hours, and then the resin was filtered out and washed with deionized water until the pH of the washed water phase was neutral, and finally the adsorption resin was placed in an oven at 120°C for 6 hours to obtain a solid amine resin adsorbent (infrared analysis diagram as shown in Figure 1 As shown), the amine exchange capacity is 11.2 mmol / g.

[0055] Comparative Example 1

[0056] The difference between this comparative example and Example 4 is that ethane-1,2-diamine hydrochloride is replaced by ethylenediamine, and its amine exchange capacity is 4.6 mmol / g.

[0057] Comparative Example 2

[0058] The difference between this comparative example and Example 4 is that ethane-1,2-diamine hydrochloride is replaced by tetramethylethylenediamine, and its amine exchange capacity is 3.5 mmol / g.

[0059] Comparative Example 3

[0060] The difference between this comparative example and Example 4 is that ethane-1,2-diamine hydrochloride is replaced by ethylenediamine (bis) hydrochloride, and no reaction occurs.

[0061] Application Example 1

[0062] 30 g of the solid amine adsorption resin prepared in Example 4 was placed in the adsorption reactor for carbon dioxide adsorption. The adsorption conditions were: carbon dioxide content in the mixed gas was 5%, adsorption temperature was 25 °C, adsorption pressure was 3.0 MPa, and adsorption space velocity was 2500 h -1 When the carbon dioxide concentration at the outlet is greater than 3%, the adsorption is stopped, the carbon dioxide adsorption capacity is calculated and the resin is regenerated by variable temperature. The regeneration conditions are a regeneration temperature of 70°C and a nitrogen purge flow rate of 400ml / min. The regeneration is terminated when the outlet carbon dioxide concentration drops to 0.0%. After the adsorption reactor is cooled to 25°C, the adsorption-desorption operation can be carried out again.

[0063] from Figure 2 It can be seen from the carbon dioxide cyclic adsorption diagram that the adsorption capacity of carbon dioxide of the adsorbent sample remains basically unchanged after 40 cycles, indicating that the adsorbent has good adsorption / regeneration stability and has good potential for industrial application.

[0064] Application Example 2

[0065] 30 g of the solid amine adsorption resin prepared in Example 4 was placed in the adsorption reactor for carbon dioxide adsorption. The adsorption conditions were: the carbon dioxide content in the mixed gas was 10%, the adsorption temperature was 25°C, the adsorption pressure was 3.0 MPa, and the adsorption space velocity was 2500 h -1 When the carbon dioxide concentration at the outlet is greater than 3%, the adsorption stops and the carbon dioxide adsorption capacity is 162 mg / g.

[0066] Application Example 3

[0067] 30 g of the solid amine adsorption resin prepared in Example 4 was placed in the adsorption reactor for carbon dioxide adsorption. The adsorption conditions were: carbon dioxide content in the mixed gas was 15%, adsorption temperature was 25 °C, adsorption pressure was 3.0 MPa, and adsorption space velocity was 2500 h -1 When the carbon dioxide concentration at the outlet is greater than 3%, the adsorption stops and the carbon dioxide adsorption capacity is 158 mg / g.

[0068] Application Example 4

[0069] 30 g of solid amine adsorption resin prepared in Comparative Example 2 was loaded into the adsorption reactor for carbon dioxide adsorption. The adsorption conditions were: carbon dioxide content in the mixed gas was 15%, adsorption temperature was 25 °C, adsorption pressure was 3.0 MPa, and adsorption space velocity was 2500 h -1 When the carbon dioxide concentration at the outlet is greater than 3%, the adsorption stops and the carbon dioxide adsorption capacity is 43 mg / g.

[0070] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.

Claims

1. A solid amine resin adsorbent, characterized in that: The structure of the solid amine resin adsorbent is as follows:

2. A method for preparing the solid amine resin adsorbent according to claim 1, characterized in that: The following steps are involved: (1) Chloromethylated resin and ethane-1,2-diamine hydrochloride in the presence of a solvent for heating reaction, after the reaction is completed, the temperature is lowered to room temperature and the solution in the reaction system is filtered, and the resin is washed with water until the pH of the water is neutral; (2) Soaking the resin obtained in step (1) with an aqueous sodium hydroxide solution, separating the resin and washing the resin with water until the pH of the water is neutral, and drying to obtain a solid amine resin adsorbent.

3. The preparation method according to claim 2, characterized in that: The particle size of the chloromethylated resin in step (1) is 500-800 μm, and the specific surface area is 20-45 m 2 / g; pore diameter is 10-25nm, pore volume is 0.05-0.3cm 3 / g.

4. The preparation method according to claim 2, characterized in that: In step (1), the solvent is one or more selected from anhydrous tetrahydrofuran, acetonitrile, dichloromethane, 1,4-dioxane, N,N'-dimethylformamide and dimethyl sulfoxide, preferably anhydrous dimethyl sulfoxide; The amount of solvent added is 200-400 mL relative to 50 g of chloromethylated resin.

5. The preparation method according to claim 2, characterized in that: In step (1), the mass ratio of the chloromethylated resin to ethane-1,2-diamine hydrochloride is 1:0.5 to 1:

1.

6. The preparation method according to claim 2, characterized in that: In step (1), the reaction temperature is 60-80°C and the reaction time is 12-24h.

7. The preparation method according to claim 2, characterized in that: In step (2), the equivalent concentration of the sodium hydroxide aqueous solution is 1-2N; In step (2), the soaking time is 12-24 hours.

8. Use of the solid amine resin adsorbent according to claim 1 or the solid amine resin adsorbent according to any one of claims 2 to 7 in decarbonization of a carbon dioxide mixed gas.

9. The use according to claim 8, characterized in that: The application comprises the following steps: loading the solid amine resin adsorbent into an adsorption reactor and adjusting the temperature to a set temperature; introducing a carbon dioxide mixed gas from the lower end of the reactor at a set flow rate and pressure, and discharging the mixed gas from the upper end after passing through the adsorbent, and connecting the discharged gas to a flue gas monitor to detect the carbon dioxide content in the gas; Preferably, the volume content of carbon dioxide in the carbon dioxide mixed gas is ≤15%; Preferably, the adsorption temperature is 10-40°C, preferably 20-40°C; the adsorption pressure is 0.1-5.0MPa, preferably 0.1-4.0MPa; the adsorption space velocity is 1000-3000h -1 , preferably 2000-3000h -1 .

10. The use according to claim 9, characterized in that: The application also includes regeneration of solid amine resin adsorbent, and the regeneration method is temperature-variable regeneration; Preferably, the regeneration temperature is 50-100°C, preferably 70-100°C, and the flow rate is 200-500 mL / min, preferably 400-500 mL / min.

Citation Information

Patent Citations

  • Room-temperature CO2 solid amine adsorbent and preparation method thereof

    CN102343254A

  • Solid amine adsorbent used for capturing low-concentration CO2 at room temperature, and preparation method and application thereof

    CN105195113A

  • A solid amine hollow fiber for removing low-concentration carbon dioxide in a closed room and a preparation method thereof

    CN112337448B

  • Functional resin containing 4,6-dimercapto-1,3,5-triazine alkali metal salt and preparation method thereof

    CN103087245A

  • Modified adsorbent and preparation method thereof

    CN110755992A